REFLECTION OF NON-MATERIAL VALUES BEHIND TAKJIL ACCOUNTING PRACTICES: A STUDY OF ISLAMIC ETHNOMETHODOLOGY - Thalib, Mohamad (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2023)
This research departs from the problem of the rise of accounting studies that focus on the corporate realm and ignore non-material values in it. This study aims to reveal the non-material values behind takjil accounting practices. This research uses the Islamic paradigm. The researcher chose this paradigm because the Islamic paradigm recognizes that accounting consists of material and non-material elements. The approach used in this study is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results of the study show that there are four accounting practices, namely cost accounting incurred by donors and mosque administrators, accounting for spiritual and emotional benefits obtained by donors when giving iftar at the mosque, simple accounting recording methods carried out by mosque administrators when receiving funds infaq from donors, and accountability for infaq costs provided by donors. The accounting practice is conditioned by non-material values in the form of sincerity, helping, and responsibility. The conclusion of this study reinforces that the essence of accounting is not only in the realm of companies but in everyday life, including when carrying out iftar activities at the mosque. Practiced accounting is not limited to material, but there are non-material values that play an essential role in shaping accounting practice.